A study using the hybrid fuzzy AHP&TOPSIS method in the conversion of a LEED-certified education building into a nearly zero-energy building in a cold climate - Celik, Ali (Strojniški vestnik, 2023)
In cold climate regions, it is essential to design and manufacture energy-efficient buildings for both economic benefits and the reduction of environmental effects by controlling energy consumption. This study aimed to increase the cost-effective energy performance and approach the nearly zero energy building (nZEB) by taking the leadership in energy and environmental design (LEED) in the cold climate region of Turkey as a model. The results of single and mixed scenarios that increase energy efficiency were determined by making energy modelling of the building. By applying single and mixed energy efficiency scenarios, a maximum saving of 85.60 % per year in terms of primary energy, an improvement of 83.6 % in terms of global costs and a reduction of 86.4 % in CO2 emissions were obtained compared to the reference building. The payback period of the scenarios is between 3.8 years and 14.53 years. The most suitable single and mixed scenario was determined by a systematic hybrid model, in which the fuzzy analytical hierarchy process (FAHP) and technique for order of preference by similarity to ideal solution (TOPSIS) methods among multi-criteria decision-making methods are used together. The results showed that economic criteria were decisive in determining the most suitable scenario for cold climate regions. The results of this study revealed that there can be a realistic decision-support model for the creation of energy-efficient buildings for countries without the need for foreign certification.
Keywords: analiza rabe energije; analiza stroškovnega optimuma; cost optimal analysis; energy analysis; fuzzy analytic hierarchy process; green buildings; mehki analitični hierarhični proces; nearly zero energy building; skoraj nič energijska stavbe; TOPSIS; zelene stavbe